Relación entre la infección por helicobacter pylori y anemia ferropénica en niños y niñas de la Escuela Tnte. Hugo Ortiz - Puichaicela Sinche, Rosa Esperanza (2015)
The Helicobacter pylori infection is worldwide highly distributed and it is considered one of the principal causes of chronic gastritis, peptic ulcers, duodenal and gastric cancer. Recently studies have shown that these could have nutritional implications, mainly in the state of iron and some vitamins therefore it leads to a delay of growth and anemia by the deficiency of iron. Reason for which it is considered to realize the study in boys and girls of the school spanish words “Teniente Hugo Ortiz”, by which determinates the infection by the H. Pylori, iron deficiency anemia, and relate the infection between H. pylori and the iron deficiency anemia. The study was descriptive and cross-sectional. The analysis was realized with 64 patients that met the inclusion criteria; a study was fulfilled in a blood sample where the hematocrit values were manually measured, the hemoglobin was obtained by a calculating factor, serum iron by using the colorimetric enzymatic method and chromatic immunoassay for the detection test of the H. pylori. Around a 62, 5% of boys and girls have the presence of the H. pylori. Around the 100% of the population that was studied we can’t see iron deficiency anemia, meanwhile in the relation of H. pylori and iron deficiency anemia there wasn’t a positive result. For all these reasons is important that both teachers and parents from the school “Teniente Hugo Ortiz” aware their children about the prevention of the Helicobacter pylori, so in case they get it they can be aware of what treatments are available to treat themselves. Keywords: Helicobacter pylori, iron deficiency anemia, hematocrit, hemoglobin, serum iron.